Tickling the Ivories: Power, Violence, Sex and Identity in Elfriede Jelinek’s The Piano Teacher. - Petersen, Kendall (My University, 2006)
This study examines the role of power and its manifestation in social and inter-personal relationships, violence, sex, and sexual identity – the construction of identity as well as the perception of identity – in Elfriede Jelinek’s novel The Piano Teacher (1988). The location of the study within a contemporary text, is intended to examine the manifestations and implications of power in contemporary society, using the relationships indicated within the text as case studies. The study attempts to indicate that social and inter-personal relationships cannot be divorced from the dynamics of power which demonstrate themselves in acts of physical, psychological and sexual violence. In light of this, the research attempts to examine the relationship between gender and power, and the manner in which it demonstrates itself in relationships. Power is also examined in light of the concept of generational conflict, through an examination of the exchange between the principal character, Erika, and her mother, and the relationship between Erika and her students, specifically a male student by the name of Walter. Furthermore the study attempts to establish the extent to which women are complicit in, and consequently perpetuate their role as victims. The examination of the relationships serves to indicate the consequences of the female adoption and consequent internalisation of traditional male power roles. Although the study is located specifically within an Austrian text, the issues raised within the text and the study are relevant to many contexts.
Master of Arts - European Literature
Keywords: piano; Elfriende Jelinek; identity; sex; violence; power; ivories